PENDEKATAN MATEMATIKA REALISTIK UNTUK MEMBANGUN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS XI IPS PADA MATERI PELUANG [REALISTIC MATHEMATICS EDUCATION IN BUILDING THE MATHEMATICS PROBLEM-SOLVING ABILITIES OF GRADE 11 SOCIAL SCIENCE TRACK STUDENTS STUDYING PROBABILITY] - Tambunan, Susiana Juseria; Sitinjak, Debora Suryani; Tamba, Kimura Patar (JOHME: Journal of Holistic Mathematics Education, 2019)
This research aims to build students’ abilities in mathematical problem-solving and to explain the uniqueness of the steps of realistic mathematic education in building the problem-solving abilities of a grade 11 (social science track) class in the study of probability at one of the schools in Kupang. The observation results found that every student was having difficulties to solving the mathematical problems, particularly the narrative questions. The research method is Kemmis and Taggart model of Classroom Action Research which was conducted in three cycles, from October 4 to November 3 with twenty-four students. Triangulation had been done to every instrument of variable. The data of mathematical problem-solving was obtained from the students by using test sheets, questionnaires, and student’s discussion sheets. Meanwhile, the data of realistic mathematic education’s variable was obtained from three sources: mentors, two colleagues, and students that were using test sheets, questionnaires, and student’s discussion sheets. The results showed that the fourteen-steps of Realistic Mathematic Education that had been done were able to build mathematical problem-solving abilities of the students. This was evidenced through the increase of three indicators of mathematical problem-solving in every cycle. The average increase of indicators of mathematical problem-solving of the grade 11 students from the first to the third cycle was 10%. Therefore, it can be concluded that the Realistic Mathematics Approach can build the ability of problem-solving of grade 11 students in a social science track studying probability at one of the schools in Kupang.BAHASA INDONESIA ABSTRACT: Penelitian ini bertujuan untuk membangun kemampuan pemecahan masalah matematis siswa dan menjelaskan kekhasan langkah-langkah pendekatan matematika realistik untuk membangun kemampuan tersebut di salah satu sekolah di Kupang kelas XI IPS pada materi peluang topik kaidah pencacahan. Pada hasil pengamatan ditemukan bahwa setiap siswa kesulitan dalam memecahkan masalah matematis khususnya soal berbentuk cerita. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas model Kemmis dan Taggart yang berlangsung selama tiga siklus, yaitu 04 Oktober – 03 November kepada 24 orang siswa. Triangulasi dilakukan pada setiap instrumen variabel. Data variabel kemampuan pemecahan masalah matematis diperoleh dari siswa menggunakan lembar tes, lembar angket, dan lembar diskusi siswa. Sedangkan data variabel tingkat pelaksanaan pendekatan matematika realistik diperoleh dari tiga sumber, yaitu mentor, dua orang rekan sejawat, dan siswa menggunakan lembar observasi, lembar angket, dan lembar wawancara. Hasil penelitian menunjukkan bahwa keempat belas langkah-langkah pendekatan matematika realistik yang terlaksana dengan baik sekali mampu membangun kemampuan pemecahan masalah matematis setiap siswa kelas XI IPS di salah satu sekolah di Kupang. Hal ini dinyatakan melalui peningkatan ketiga indikator pemecahan masalah matematis di setiap siklus. Peningkatan rata-rata indikator pemecahan masalah matematis siswa kelas XI IPS dari siklus pertama sampai ketiga adalah sebesar 10%. Oleh karena itu, dapat disimpulkan bahwa pendekatan matematika realistik dapat membangun kemampuan pemecahan masalah matematis siswa kelas XI IPS di salah satu sekolah di Kupang pada materi peluang topik kaidah pencacahan.